Ap. Claudio Pulcro, cónsul deI 54 aC. - Muñíz Coello, J. (Gerión. Revista de Historia Antigua, 2003)
Appius Claudius Pulcher’s biography is developed largely in the shade of the political career of M. Cicero, his successor in Cilicia’s government. We are dealing with a hard and genuine member of the old patrician aristocracy, perhaps the last one of a geos. the Pulcrhii who was competent to assume a leadership in the most arduous century of the Republic. We examine his political ambition, his strong ties and familiar profits in Cilicia, and the institutions and state’s singular notion who show in the filling of the augur and censorship.